THE EFFECTIVENESS OF USING VIDEO-BASED LEARNING MEDIA ON LEARNING MOTIVATION OF STUDENTS OF CLASS X SMA NEGERI 3 SAMARINDA - Halifahtul Wahda Nia; Sudarman Sudarman; Vitria Puri Rahayu (Faculty of Teacher Training and Education, Mulawarman University, 2022)
The use of learning media is one of the efforts that can be used by teachers to increase students' learning motivation. One of the learning media that can be used is video-based learning media. This study aims to determine the effectiveness of video-based learning media on the learning motivation of class X students of SMA Negeri 3 Samarinda. The subjects in this study were students of class X A as the experimental class and XE as the control class. The type of research used is experimental research with posttest only control group design. Based on the results of the study, it was found that video-based learning media had an effect on the learning motivation of class X students at SMA Negeri 3 Samarinda. This can be seen from the results of the posttest and the results of observations as supporting data. The difference in posttest scores in the experimental class was superior when compared to the control class. The test used in this study is the Mann Whitney test as an alternative to test the research hypothesis and it can be concluded that H0 is rejected or Ha is accepted, which means that video-based learning media is effective on the learning motivation of class X students at SMA Negeri 3 Samarinda.